The age of sustainable development - Sachs, Jeffrey D. 1954-; Ki-Moon, Ban (New York Columbia University Press, 2015)
Jeffrey D. Sachs is one of the world's most perceptive and original analysts of global development. In this major new work he presents a compelling and practical framework for how global citizens can use a holistic way forward to address the seemingly intractable worldwide problems of persistent extreme poverty, environmental degradation, and political-economic injustice: sustainable development. Sachs offers readers, students, activists, environmentalists, and policy makers the tools, metrics, and practical pathways they need to achieve Sustainable Development Goals. Far more than a rhetorical exercise, this book is designed to inform, inspire, and spur action. Based on Sachs's twelve years as director of the Earth Institute at Columbia University, his thirteen years advising the United Nations secretary-general on the Millennium Development Goals, and his recent presentation of these ideas in a popular online course, The Age of Sustainable Development is a landmark publication and clarion call for all who care about our planet and global justice.
Keywords: Desarrollo económico -- Aspectos ambientales; Desarrollo sostenible